Підвищення професійного рівня керівників сільських загальноосвітніх шкіл - Замлинська, О. В. (НТУ "ХПI", 2011)
She comprehensive school management is the most popular and more than other fakes into consideration all the factors of impact on school guarantees the most important features of today’s changes in the education system. And this makes the professional competence of the school head significant; reveal the importance of head’s readiness to execute the management functions including social-pedagogical work conditions of school.
Keywords: професійна компетентність; педагогічна культура; професійна майстерність